Reliability and Integrity in Lightweight Data Exchange for Mobile Cloud Computing - Bhosale, KS; Kshirsagar, MR; Jadhav, KL; Sayyad, SG (International Journal of Computer Sciences and Engineering, 2020)
Cloud computing being the latest technology, the storage and retrieval of personal data from mobile devices can be done from any location at anytime. The data security problem in mobile cloud is preventing development of mobile cloud. Studies have been conducted in various aspects to provide improved solutions to the cloud security. As mobile devices only have limited power and computing resources most of the solutions are not favorable for mobile cloud.. In this paper, we propose a reliable lightweight data exchange scheme for mobile cloud computing. The results show that the overhead on the mobile device side when users are sharing data in mobile cloud environments is effectively reduced using this technology.If the user wants to upload or download the data publicly then there wont be any encryption made over that data and if the data is confidential then certain algorithms for encryption can be applied to maintain the integrity.